2013
DOI: 10.3800/pbr.8.68
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the net growth rate of the cyanobacterium Cylindrospermopsis raciborskii in a shallow artificial pond in northern Taiwan

Abstract: Abstract:The seasonal dynamics and the net growth rates of the planktonic freshwater cyanobacterium Cylindrospermopsis raciborskii were monitored in a shallow artificial pond in northern Taiwan from February 2010 to January 2011. C. raciborskii was present in the pond throughout the study, and its abundance was positively correlated with water temperature. The net growth rates of C. raciborskii displayed no clear seasonal pattern, whereas the highest value (0.184 d 1 ) was observed in early July when the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The result suggested that the high water temperature may play a key role in regulating the presence of R. raciborskii in Ea Nhai reservoir. Similar results were found in previous studies [38][39][40]. So far, R. raciborskii has successfully invaded many regions from tropical and subtropical towards temperate zones.…”
Section: Concentrations Of Cylindrospermopsinsupporting
confidence: 91%
“…The result suggested that the high water temperature may play a key role in regulating the presence of R. raciborskii in Ea Nhai reservoir. Similar results were found in previous studies [38][39][40]. So far, R. raciborskii has successfully invaded many regions from tropical and subtropical towards temperate zones.…”
Section: Concentrations Of Cylindrospermopsinsupporting
confidence: 91%
“…4), implying that the rapid decline in the abundance in late July 2011 occurred in the middle of the formation of a bloom. Rainfall is a factor that can rapidly -although often only temporarily -reduce the abundance of C. raciborskii during the growing season (Yamamoto et al, 2013). However, no strong rainfall was recorded from mid-to late July 2011 in Taipei (Central Weather Bureau, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, C. raciborskii is widely distributed in eutrophic ponds (Yamamoto et al, 2011). Surveys of a pond in northern Taiwan have demonstrated that C. raciborskii exhibits typical seasonal dynamics, with a low population density in winter and dominating in summer (Yamamoto and Shiah, 2012;Yamamoto et al, 2013). However, extended monitoring has shown that C. raciborskii sometimes exhibits atypical seasonal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In pelagic region of typical dimictic lakes with large water surface area, seasonal variations in phytoplankton abundance of the surface water are relatively predictable and mainly affected by water temperature and nutrient supply in the water column by seasonal vertical mixing. On the other hand, water retention time or water exchange rate become more important factors in water systems with highly susceptible to variable influent quantities such as small lakes and ponds, upstreams of river-mouth dams, and riverine and transitional zones of reservoirs (e.g., Thornton et al 1990;Hodoki and Murakami 2007;Yamamoto et al 2013). Lake Hira is small and shallow, and previous study also showed that nutrients (DIP and DIN) are usually remaining in the water (Mitamura et al 2014) and seem not to become limiting factors for phytoplankton growth.…”
Section: Discussionmentioning
confidence: 99%